Synthesis and Antiproliferative Effect of Ethyl 4‐[4‐(4‐Substituted Piperidin‐1‐yl)]benzylpyrrolo[1, 2‐a]quinoxalinecarboxylate Derivatives on Human Leukemia Cells. (5th April 2017) - Desplat, Vanessa; Vincenzi, Marian; Lucas, Romain; Moreau, Stéphane; Savrimoutou, Solène; Rubio, Sandra; Pinaud, Noël; Bigat, David; Enriquez, Elodie; Marchivie, Mathieu; Routier, Sylvain; Sonnet, Pascal; et al.
Abstract: Acute leukemia is a hematological malignancy with high incidence and recurrence rates and is characterized by an accumulation of blasts in bone marrow due to proliferation of immature lymphoid or myeloid cells associated with a blockade of differentiation. The heterogeneity of leukemia led us to look for new specific molecules for leukemia subtypes or for therapy‐resistant cases. Among heterocyclic derivatives that attracted attention due to their wide range of biological activities, we focused our interest on the pyrrolo[1, 2‐ a ]quinoxaline heterocyclic framework that has been previously identified as an interesting scaffold for antiproliferative activities against various human cancer cell lines. In this work, new ethyl 4‐[4‐(4‐substituted piperidin‐1‐yl)]benzylpyrrolo[1, 2‐ a ]quinoxalinecarboxylate derivatives (1 a –o ) were designed, synthesized, and evaluated against five different leukemia cell lines, including Jurkat and U266 (lymphoid cell lines) and K562, U937, and HL60 (myeloid cell lines), as well as on normal human peripheral blood mononuclear cells (PBMCs). This new pyrrolo[1, 2‐ a ]quinoxaline series showed interesting cytotoxic potential against all tested leukemia cell lines. In particular, pyrroloquinoxalines1 a and1 m, n seem to be interesting due to their high activity against leukemia and their low activity against normal hematopoietic cells, leading to a high index of selectivity. Abstract : An antileukemia army : New ethyl 4‐[4‐(4‐substituted piperidin‐1‐yl)]benzylpyrrolo[1, 2‐ a ]quinoxalinecarboxylate derivatives were designed, synthesized, and evaluated against five leukemia cell lines, as well as normal human peripheral blood mononuclear cells. These new pyrrolo[1, 2‐ a ]quinoxalines showed interesting cytotoxic potential against all leukemia cell lines tested, with three pyrroloquinoxalines having particularly high activity against leukemia and low activity against normal hematopoietic cells.